Entrepreneurship in Africa : a study of successes - Fick, David S. (Quorum Books, 2002)
An upclose look at the women and men who have achieved success, wealth, and recognition in their African homelands, how they accomplished it, and how they are now giving back to their nations and societies--at least as much as they received. This is a journey through the economic world of Africa--an account, often in their own words, of Africans who achieved success, wealth, and recognition in their own homelands and how they did it. Entrepreneur Dave Fick interviewed several hundred women and men who were willing to assume risks, often spectacular ones, for personal economic gain--but who did it legally, ethically, and who are now giving back to their nations and societies at least as much as they received. They speak openly of their hardships and failures, what they did right and what they did wrong, and their accounts are remarkable.; We gain insight into the way business must be done under harsh political and economic circumstances, but we also learn unusual techniques and strategies that others in more favorable milieus can use to accomplish similar feats: With commentaries from notable scholars and other businesspeople and with Fick's own first-hand onsite observations, the book is a self-educating colloquiem, a collection of personal meetings, accounts, letters, emails and telephone calls between Fick, his counterparts in Africa, and others around the world. It is also an attempt to encourage a dialogue that will accelerate the exchange and spread of knowledge and ideas, and a way to help the people of Africa build a peaceful and better society for themselves and the world.